2018
DOI: 10.1002/pon.4794
|View full text |Cite
|
Sign up to set email alerts
|

Are psychological interventions effective on anxiety in cancer patients? A systematic review and meta‐analyses

Abstract: Low psychological distress at baseline and nonevidence-based interventions were the main factors identified for low effectiveness. Screening and assessment to determine clinical levels of anxiety in patients with cancer should be considered in future trials as an inclusion criterion before providing psychological interventions. Systematic review registration: PROSPERO: International Prospective Register of Systematic Reviews: CRD42017056132.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 111 publications
4
39
1
Order By: Relevance
“…Currently, screening is recommended in clinical practice as well as for trial recruitment, but in our trial screening (which was part of standard care) proved little effective in terms of detecting individuals with care needs. Only 1.0% of the approached individuals participated in the RCT.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Currently, screening is recommended in clinical practice as well as for trial recruitment, but in our trial screening (which was part of standard care) proved little effective in terms of detecting individuals with care needs. Only 1.0% of the approached individuals participated in the RCT.…”
Section: Discussionmentioning
confidence: 95%
“…As a means to reflect on reasons why an RCT following high‐quality methodological standards failed to work in clinical practice, this observational study examined the reasons for nonparticipation in the RCT and the demographic and medical characteristics of depressed survivors that did (not) participate. Cancer survivors in our trial were consecutively screened on depressive symptoms as a part of standard care, as recommended by the current clinical screening guidelines and regarded as a quality standard in setting up an RCT . Yet, the screening procedure was not efficient (ie, resulting in low uptake).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in the context of consent rates that, while varied, had a median of less than a third of those approached across the studies, meaning that while many caregivers were eligible, this did not translate to enrolment. A recent systematic review and meta‐analysis exploring the efficacy of psychological interventions on anxiety in cancer patients found that low psychological distress at baseline was a key reason for low effectiveness, with authors advocating for screening and assessment of anxiety as an inclusion criterion before enrolment in psychological interventions . Caregivers not experiencing a problem may have low motivation to spend time in an intervention study they see as not relevant to their situation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis exploring the efficacy of psychological interventions on anxiety in cancer patients found that low psychological distress at baseline was a key reason for low effectiveness, with authors advocating for screening and assessment of anxiety as an inclusion criterion before enrolment in psychological interventions. 63 Caregivers not experiencing a problem may have low motivation to spend time in an intervention study they see as not relevant to their situation. Others have noted the need to increased research for vulnerable caregiving populations and risk stratification to target those most in need of support.…”
Section: Discussionmentioning
confidence: 99%